Fostering a Green Future: The Role of Environmental Education in Community Empowerment - Tanveer, Muhammad (International Journal of Energy Economics and Policy, 2025)
The present research examines how community engagement, community empowerment, and environmental education affect environmental sustainability in the industrial sector of Pakistan particularly among the working employees of the HEIs. A survey research design was adopted and a self-developed structured questionnaire adopted from research conducted in similar studies was used in gathering data from 322 participants in different capacities in HEIs. The participants included clerical workers up to managerial level like deans of the colleges to increase the generalizability of the results. Smart partial least squares structural equation modeling was employed to analyze the data to explore the links between the constructs under investigation as well as their impact on environmental sustainability. The analysis showed that there were positive relations between community engagement and environmental education and environmental sustainability and that community engagement had the strongest relationship. Community empowerment was another variable that was positive with environmental sustainability albeit with a much smaller effect size compared to the others. Community engagement and community empowerment were discovered to have a limited moderating effect which has led to the understanding that their direct contribution to sustainability is greater than their moderation role. Therefore, the results highlight the need to continue encouraging community participation and environ mental awareness in order to encourage sustainable behavior. The findings of this research would be of great interest to policymakers, educators, and industry players interested in bolstering environmental sustainability initiatives within the Pakistani industry.